Clinical Results and Aortic Remodeling After Endovascular Treatment for Complicated Type B Aortic Dissection With the “Fabulous” Stent System - Wang, Ruihan; Kan, Yuanqing; Yang, Mou; Zhang, Hongkun; Zhang, Xiaoming; Dai, Xiangchen; Zhai, Shuiting; Hu, Hejie; Zhang, Xiwei; Chen, Bing; Huang, Jianhua; Qin, Xiao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To report the clinical outcomes and aortic remodeling after the implantation of a self-developed, biomechanically optimized, two-stage thoracic stent system named Fabulous. Background Given the efficacy of the PETTICOAT concept, the benefits of Fabulous and the behavior of remodeling in different segments need further investigation. Methods This is a prospective and multicenter study. From 2017 to 2019, 145 patients (mean age, 56.6 years; 88.3% male) from 14 centers were included in this cohort. The clinical results and core laboratory results were from a central electronic data capture system. Computed tomographic angiography was performed preoperatively, 1 month, 6 months and yearly thereafter and was used for volumetric analysis by 3mensio (Bilthoven, The Netherlands). After the 1-year follow-up, 97.2 and 87.6% of the clinical and imaging results of the eligible patients were available. Results Both stent grafts and bare stents were successfully delivered in place in 100% of the patients. The 30-day mortality and 1-year freedom from all-cause mortality were 2.1 and 96.6%, respectively. The incidence of entry flow was 11.7% at 30 days and 6.2% at 365 days. No cases of stent-induced new entry (SINE) or reintervention were observed. After the 1-year follow-up, the true lumen/overall volume ratio reached 88%. The following subdivided segment volume changes were recorded: stent graft segment TL +56%; FL −92%, bare stent segment TL +32%; FL −75%, and there were no significant changes in the visceral segment. Conclusions These outcomes indicated that there were favorable clinical benefits of Fabulous stent system. This device achieved a low short-term mortality and a low incidence of reintervention. In addition, patients undergoing Fabulous stent system implantation showed remodeling both on descending aorta and on the distal aorta. The volume changes in the TL and FL varied in the different segments. The long-term follow-up is still ongoing.